Late starters or excluded generations? A cohort analysis of catch up in homeownership in England - Renata Bottazzi; Thomas F. Crossley; Matthew Wakefield (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We investigate whether initial differences in speed of entry into homeownership lead to longlasting differences in ownership between generations. Our data span nearly forty years and multiple cycles of England's very volatile house prices. We document that ownership rates at thirty have differed substantially, with a significant negative association with prices. To assess the persistence of these differences we use synthetic cohort methods. Measurement error problems - attenuation and other biases - complicate the analysis. Two methods of dealing with this both indicate that cohorts with low ownership rates at thirty close about 80% of the ownership gap by forty.
Keywords: R21; R31; 330; homeownership; synthetic cohort data; measurement error; Wohneigentum; Kohortenanalyse; Statistischer Fehler; Schätzung; England